O anticomunismo nas aulas de história: e-book temático para o ensino médio - Alves, Eliene Gomes da Silva (2024)
The research aims to work on the anti-communist imaginary in High School History classes, highlighting its influence on the coups d'état of 1937, 1964 and 2016. It was argued that the coups d'état that occurred in Brazil during the republican period had the anti-communist imaginary as an extremely relevant mobilizing factor. To this end, it presents the anticommunist imaginary as a political and ideological phenomenon, socially and historically constructed, through representations that undergo constant updates and are used strategically in moments of institutional and political crisis. The aim was to show that these representations feed imaginaries which are internalized in the collective unconscious and contribute to the perpetuation of discourses, authoritarian and denialist practices that violate democracy and Human Rights in Brazil. Using the New Political History as a historiographical approach, the research analyzed the anti-communist imaginary as a power strategy that uses images, speeches, behaviors, myths, symbols and beliefs with political purposes and uses. It is expected that the study and reflection on the trajectory of communism and anti-communism in Brazil will contribute to History teaching committed to strengthening democratic feelings and attitudes and reduce the (verified) scarcity of research that addresses anti-communism in Education Basic. The pedagogical strategy adopted for this purpose was the creation of a thematic E-book, which can be used by High School History teachers, especially in the Federal District, as training itineraries, pedagogical projects or a diversified part